Exploring glycoform-dependent dynamic modulations in human immunoglobulin G via computational and experimental approaches - Saeko Yanaka; Yoshitake Sakae; Yohei Miyanoiri; Takumi Yamaguchi; Yukiko Isono; Sachiko Kondo; Miyuki Iwasaki; Masayoshi Onitsuka; Hirokazu Yagi; Koichi Kato (Proceedings of the National Academy of Sciences, 2025)
We investigate the impact of glycoform alterations on the dynamic structure of the human immunoglobulin G1 (IgG1) Fc region using integrated computational and experimental approaches. Four distinct IgG1-Fc glycoforms, varying in core fucosylation and nonreducing terminal galactosylation, were generated through a combination of cell engineering and in vitro enzymatic reactions. Stable-isotope-assisted NMR spectroscopy, incorporating both glycan and protein signals, revealed that galactosylation induces chemical shift perturbations extending from the glycan–protein interface to the C H 2–C H 3 domain boundary. Molecular dynamics simulations demonstrated that the absence of galactose enhances the mobility of both the glycan and the C H 2 domain, broadening the conformational landscape of the Fc quaternary structure. This increased flexibility likely contributes to a greater entropic penalty upon binding to effector molecules, which constrain the Fc in an asymmetric conformation. Conversely, the effects of fucosylation are more localized, primarily influencing the dynamics of residues involved in Fcγ receptor IIIa binding. These findings provide atomic-level insights into the distinct yet synergistic mechanisms by which galactosylation and fucosylation modulate IgG1-Fc dynamics and effector functions, offering crucial information for the optimization of therapeutic antibodies.